How many tables should i have? Decision support systems for restaurants management - Sakay-Rodríguez, Óscar Eduardo (2014)
This article shows the benefits that a restaurant which uses Information Technologies (IT) as a strategic tool for management would get. The restaurant where the study was carried out, has a model for operations management, whose indicators use variables in terms of profitability and resource utilization in an independent manner, not related; the disadvantage is the inability to measure the profitability in terms of resource utilization. For this reason, a mixed indicator was used: REVPASH (revenue per available seat hour), which made it possible to measure the profitability of the restaurant in terms of the use of its resources. Taking this into consideration, a Decision Support System was developed that allowed us to determine the optimal combination of tables, improving the profitability of the restaurant according to the composition of the groups of guests, the high-demand times in the restaurant, among other things.